Addressing of Global Environmental Problems and the Solutions: A Bibliometric Analysis - H. Husamah; Vivi Indriani; Hanik Fitrotul Azizah; Abdulkadir Rahardjanto; Tutut Indria Permana; Ahmad Adnan Mohd Shukri (Al Jahiz, 2025)
Environmental problems and their solutions demand a holistic approach to address key challenges effectively. Previous studies have included reviews but lacked bibliometric analysis. This study bridges the gap by conducting a bibliometric analysis of research on "environmental problems and their solutions" using data from the Scopus database. Applying the PRISMA method, 39 articles were selected from an initial 353 documents. Analytical tools like Scopus, VOSviewer, and RStudio were utilized to visualize bibliometric relationships, temporal trends, collaboration patterns, and key themes. Research distribution from 1990 to 2023 fluctuated, with notable peaks in certain years. The United States leads global contributions, followed by Russia, Germany, and Turkey. Strategic themes such as "environmental problems" and "water treatment" were prominent, while "energy resources" remained a developing theme. This study offers a strategic map for understanding environmental research landscapes, fostering global collaboration, and shaping future multidisciplinary research strategies focusing on energy transitions and sustainable innovations.